IMPLEMENTATION OF ICT-BASED LEARNING MANAGEMENT MODELS AT MTS AL-AMIN TABANAN - Muhammad Dzul Aidi (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to develop the application of ICT-based learning models. With these tools and models, Madrasahs can easily monitor and evaluate the education process. This research was conducted with Research and Development. The research location is at MTs Al-Amin Tabanan, and data collection uses interviews, observation and documentation. Data were analyzed using descriptive analysis and triangulation techniques to test data validation. The results of the research are: The first step is making decisions on ICT-based learning, the second step is planning ICT-based learning, the third step is implementing ICT-based learning, the fourth step is evaluating ICT-based learning. The key factor for the success of this model is in the second step, namely how the teacher creates lesson plans and collaborates with all parties related to managing ICT-based learning.